Correlational analysis of three-dimensional spinopelvic parameters with standing balance and gait characteristics in adolescent idiopathic scoliosis: A preliminary research on Lenke V - Liu, Yanan; Li, Xianglan; Dou, Xiaoran; Huang, Zhiguan; Wang, Jun; Liao, Bagen; Zhang, Xiaohui (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Adolescent idiopathic scoliosis (AIS), the most common spinal deformity, possibly develops due to imbalanced spinal loading following asymmetric development. Since altered loading patterns may affect standing balance and gait, we investigated whether a correlation exists between balance ability, gait pattern, and the three-dimensional radiographic spinopelvic parameters in AIS patients. Methods: A cross-sectional observational study was conducted with 34 AIS patients (aged 10–18 years) and an equal number of healthy age and sex-matched teenagers (normal group). We obtained the spinopelvic three-dimensional parameters and balance parameters simultaneously through the EOS imaging system and gait and center of pressure (CoP) characteristics using a plantar pressure measurement mat. Besides determining the intergroup differences in balance and gait parameters, multiple linear regression analyses were performed to identify any correlation between the static plantar pressure and radiographic parameters. Results: Compared to the normal group, the CoPx, CoP path length, and 90% confidence ellipse area were significantly higher in AIS patients (AIS: −13.7 ± 5.7mm, 147.4 ± 58.1mm, 150.5 ± 62.8mm2; normal: −7.0 ± 5.4mm, 78.8 ± 32.0mm, 92.1 ± 41.7mm2, respectively), correlated with apical vertebra translation, sagittal pelvic tilt, and pelvis axial rotation, respectively. Moreover, AIS patients had a shorter stance phase (61.35 ± 0.97 s vs. 62.39 ± 1.09 s), a longer swing phase (38.66 ± 0.97 s vs. 37.62 ± 1.08 s), and smaller maximum pressure peaks in the gait cycle, especially on the left foot, as compared to healthy subjects. Moreover, the CoP trajectory in AIS patients was different from the latter, and changes in the bipedal trend were not consistent. Conclusion: The standing balance and gait characteristics of AIS patients are different from those of healthy subjects, as reflected in their three-dimensional spinopelvic radiographic parameters.